PENILAIAN KUALITAS HIDUP PASIEN PARKINSON MENGGUNAKAN PDQ39 DAN KORELASINYA DENGAN TINGKAT KEPARAHAN PENYAKIT - Debby Amelia, Thamrin Syamsudin, Ahmad Rizal Ganiem (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION THE IMPORTANCE OF HEALTHRELATED QUALITY OF LIFE HAS BEEN INCREASINGLY EMPHASIZED ESPECIALLY IN PATIENTS WITH CHRONIC PROGRESSIVE AND DEGENERATIVE DISORDERS LIKE PARKINSONS DISEASE PD THEREFORE THE INSTRUMENT TO MEASURE QUALITY OF LIFE BECOME IMPORTANT THE 39ITEM PARKINSONS DISEASE QUESTIONNAIRE PDQ39 IS THE MOST WIDELY USED PATIENTREPORTED SCALE TO ASSESS THE QUALITY OF LIFE IN PARKINSONS DISEASE